S-IgA Levels and Urinary Tract Mucosal Fluid Secretion: An In Vivo Study of the Effectiveness of Etlingera elatior Extract Therapy - Sari, Mita; Hujjatusnaini, Noor; Nur Indah Sari, Lilin Ika; Tuanfareena, Tuanfareena (Jurnal Medika Veterinaria, 2025)
Mucosa surface is the body's initial barrier against pathogens, rely on secretory Immunoglobulin A (s-IgA) for localized immunity. This study investigated the impact of Etlingera elatior extract on s-IgA levels and mucosal fluid secretion in mice challenged with Staphylococcus aureus. The research method used an experimental design with seven treatment groups, i.e negative control (P1), positive control (P2), and five groups with E. elatior extract administration at concentrations of 40% to 80% (P3-P7). Data were analyzed using ANOVA and Tukey's subset test to determine differences between groups. The results showed an increase in s-IgA levels as the extract concentration increased, with the highest level at P7 (1842.25 ng/mL). Conversely, mucosal fluid secretion decreased, with the lowest level at P7 (21.5 L). Statistical analysis showed significant differences between treatment groups (p0.05). The increase in s-IgA levels and normalization of mucosal fluid secretion are thought to be caused by bioactive content such as flavonoids and alkaloids which have immunostimulant and anti-inflammatory properties. The study revealed that E. elatior extract is effective in increasing s-IgA levels while controlling mucosal fluid secretion in mice infected with Staphylococcus aureus. These findings suggest the potential of E. elatior extract as a natural potential immunostimulant to support the treatment of mucosal infections.